Analisis Peran Hukum Dagang dalam Memberikan Kepastian Hukum terhadap Transaksi Perdagangan di Era Digital - Nabila Rinjani Sayidatun Nisa; Hudi Yusuf (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analysis the role of commercial law in providing legal certainty for trade transactions in the digital era. The evolution of modern commerce has transformed the legal relationships among business actors, consumers, electronic system operators, payment service providers, and other parties involved in the distribution chain of goods and services. These changes have created a need for a legal framework capable of guaranteeing transaction validity, consumer protection, business actor liability, personal data security, and dispute resolution mechanisms. This study employs a normative-juridical method, utilizing both statutory and conceptual approaches. Primary legal sources include the Commercial Code, the Civil Code, the Trade Law, the Consumer Protection Law, the Law on Electronic Information and Transaction (as amended), the Government Regulation on Trade Through Electronic Systems, and the Personal Data Protection Law. The analysis reveals that commercial law serves as an instrument for regulation, protection, and the assurance of legal certainty in modern trade activities. However, its implementation faces challenges such as the rapid evolution of digital business models, the use of standard contract clauses, risks regarding personal data, low public legal literacy, and jurisdictional complexities in cross-regional transaction.